Scepticism and literature an essay on Pope, Hume, Sterne, and Johnson - Parker, G. F. (Graham Frederick) 1956- (Oxford University Press, 2003)
This study of the role of scepticism in literature offers an introduction to key issues in 18th-century literature and philosophy. Parker traces the presence of sceptical thinking in works by Pope, Hume, Sterne, & Johnson & relates it more broadly to the social self-consciousness of 18th-century culture.